Kearifan Lokal Masyarakat Desa Saga dalam Pelaksanaan Konservasi Alam Sebagai Desa Penyangga Taman Nasional Kelimutu - Sanjina Paul De Jesus; Maria M. E. Purnama; Fadlan Pramatana; Roni Haposan Sipayung (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
This research has been carried out in Saga Village, Ende Regency, East Nusa Tenggara Province in July-August 2023. This study aims to determine the relationship between local wisdom and nature conservation in Saga Village in maintaining forest sustainability. The method used in this study is the descriptive method. The data in this study was collected through observation, interview and documentation techniques directly in the field using the snowball sampling method in order to obtain information and obtain appropriate and accurate data. The results of research on local wisdom as a prevailing view of life in the people of Saga Village affect the preservation of forests that are useful from generation to generation where there are customs and customs that prevail today. The prevailing tradition is Pire which states several rules that must be obeyed by all villagers and other buffer villages of Kelimutu National Park. The applicable prohibitions must not be violated, if violated, they will be subject to customary sanctions given by traditional elders or called Mosalaki. The Saga Village community also carries out conservation activities that help the Kelimutu National Park which participates in reforestation, protects springs, conducts area security or patrols with the Fire Care Community (MPA), conducts biophysical inventory by recording the potential in forest areas, checks springs in forest areas and the potential of flora and fauna.